PEDAGOGICAL FUTUROLOGY: 21ST CENTURY PROSPECTS - HARUTIUNYAN, Nazik; MKHITARYAN, Zarine (Вісник Черкаського національного університету імені Богдана Хмельницького. Серія: "Педагогічні науки", 2020)
The article discusses the subject of futurology, the development of different scenarios of foreseeing about the future of mankind, the role and place of education in them. In particular, the article presents the viewpoint that at present Pedagogical Futurology lacks the necessary fundamental, world-wide conceptions about the man of future, without which the existence of human development today and tomorrow will be jeopardized.